2016
DOI: 10.1177/1479164116645583
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal echocardiography in patients with type 2 diabetes and relation to symptoms and clinical characteristics

Abstract: Objectives: We aimed to determine the prevalence of echocardiographic abnormalities and their relation to clinical characteristics and cardiac symptoms in a large, contemporary cohort of patients with type 2 diabetes. Results: A total of 1030 patients with type 2 diabetes participated. Echocardiographic abnormalities were present in 513 (49.8%) patients, mainly driven by a high prevalence of diastolic dysfunction 178 (19.4%), left ventricular hypertrophy 213 (21.0%) and left atrial enlargement, 200 (19.6%). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
40
4
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 44 publications
3
40
4
2
Order By: Relevance
“…Patients are referred to these clinics because of inadequate glycaemic control or diabetes‐related complications, and treatment is intensified with a multidisciplinary approach. All patients in the clinics were eligible to participate in the Thousand&2 Study . A total of 1030 patients (participation rate, 47.8%) were included.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients are referred to these clinics because of inadequate glycaemic control or diabetes‐related complications, and treatment is intensified with a multidisciplinary approach. All patients in the clinics were eligible to participate in the Thousand&2 Study . A total of 1030 patients (participation rate, 47.8%) were included.…”
Section: Methodsmentioning
confidence: 99%
“…All patients in the clinics were eligible to participate in the Thousand&2 Study. 8 A total of 1030 patients (participation rate, 47.8%) were included. For the present analyses, 224 patients were excluded (n = 7, prior heart valve replacement; n = 21, atrial fibrillation; n = 87, missing laboratory values; n = 109, missing echocardiographic measurements).…”
Section: Study Populationmentioning
confidence: 99%
“…What do we know about HFpEF in T2DM patients? In a cross‐sectional echocardiographic study in 1000 T2DM patients, risk factors for development of HFpEF were common: diastolic dysfunction (20%), left ventricular hypertrophy (20%) and left atrial enlargement (20%) . Furthermore, screening identifies undiagnosed HFpEF in 20–25% of T2DM patients .…”
mentioning
confidence: 99%
“…Except for LVDD, other echocardiographic changes that can be found in type 2 diabetes patients [10,17] are left ventricle remodeling and hypertrophy [18], reduced EF [19], dilated left atrium [19], and valvular impairment [20]. These disorders could be diagnosed early in the course of the diabetes progression and often remain asymptomatic [19]. Jorgensen et al found echocardiographic abnormalities in 49,8% of 1030 outpatients with DM2 and the prevailing alterations were LV hypertrophy, dilated left atrium and LVDD [19].…”
mentioning
confidence: 99%